(untitled) (SCIÉNDO INGENIUM, 2021)
It was investigated why sex induced by deception with partner impersonation that vitiates the consent of the victim, has relevance for Peruvian Criminal Law and its autonomous classification is justified. The sample consisted of 07 cases of sex induced by deception with partner impersonation at the national and international level, period 2009 - 2019; as well as by the National and Comparative Legislation of the State of Indiana, Iowa, California, Argentina and Spain, which regulates it; and, to complement the information, a personal sample of 120 criminal lawyers from Trujillo was considered to collect specialized information regarding the subject of study. The techniques of documentary analysis and the survey were used. The information obtained was statistically processed and the results were discussed with the methods of Science and it was determined that sex induced by deceit with partner impersonation, which vitiates the consent of the victim, has relevance for Peruvian Criminal Law, because It enables the crime of rape through deception with spoofing of a partner to be classified as an autonomous figure de lege ferenda, giving greater protection to the legal right of Sexual Freedom, in accordance with the Principle of Legality.